2014
DOI: 10.1016/j.bbr.2014.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Temporally-patterned deep brain stimulation in a mouse model of multiple traumatic brain injury

Abstract: We report that mice with closed-head multiple traumatic brain injury (TBI) show a decrease in the motoric aspects of generalized arousal, as measured by automated, quantitative behavioral assays. Further, we found that temporally-patterned deep brain stimulation (DBS) can increase generalized arousal and spontaneous motor activity in this mouse model of TBI. This arousal increase is input-pattern-dependent, as changing the temporal pattern of DBS can modulate its effect on motor activity. Finally, an extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 47 publications
(49 reference statements)
0
27
0
Order By: Relevance
“…This network activation is associated with improvements in learning, working memory, arousal system, and waking of rat from asleep. [10,25,26] Recovery of somatosensory function among rats was associated with intact myelinated fibers connecting thalamic nucleus and somatosensory cortex as was evidenced by blood-oxygen-level-dependent response of magnetic resonance imaging (MRI) scan. [27] TBI rats treated with allopregnanolone had shown better performance in spatial performance task; allopregnanolone, a metabolite of progesterone, has shown to enhance gamma-aminobutyric acid neurotransmission in mediodorsal nucleus of thalamus.…”
Section: Preclinical and Histopathological Studies Evidence Of Thalammentioning
confidence: 99%
“…This network activation is associated with improvements in learning, working memory, arousal system, and waking of rat from asleep. [10,25,26] Recovery of somatosensory function among rats was associated with intact myelinated fibers connecting thalamic nucleus and somatosensory cortex as was evidenced by blood-oxygen-level-dependent response of magnetic resonance imaging (MRI) scan. [27] TBI rats treated with allopregnanolone had shown better performance in spatial performance task; allopregnanolone, a metabolite of progesterone, has shown to enhance gamma-aminobutyric acid neurotransmission in mediodorsal nucleus of thalamus.…”
Section: Preclinical and Histopathological Studies Evidence Of Thalammentioning
confidence: 99%
“…Potentially important for therapeutic translation of these findings, these effects were also observed in a model of traumatic brain injury [Tabansky et al 2014], although with somewhat different effects of specific patterns than observed in the arousal studies on healthy animals.…”
Section: Pattern Mattersmentioning
confidence: 96%
“…Grouped by indications of interest, recent work in rodents and higher mammals is summarized in Table 1 . 121 , 131 149) …”
Section: Animal Modelsmentioning
confidence: 99%